Financial literacy among brazilian university students: An investigation based on OECD criteria - Krause, Regiane; Niehues, Andrea Luisa da Silva; Aquino, Roger Freitas de; Souza, Julio Cesar Lopes de (Seven Editora, 2023)
This study aims to verify the Financial Literacy of Higher Education students, considering the behavior, consumer attitude and knowledge related to investments and financial organization. In addition, sociodemographic variables such as age, gender and income were considered. Financial Literacy was assessed through the dimensions financial knowledge, organization and financial attitude, correlated with sociodemographic variables. To run the model, a survey was conducted sent to university students from all undergraduate courses of the university under study, resulting in 276 respondents. The information was analyzed using the Multiple Linear Regression (MLR) technique. The motivation for conducting this study is to identify whether university students are financially literate and whether this literacy is affected by socioeconomic and demographic variables. It was found that, among other results, the respondents in the sample have a self-perception that they deal with their money, avoiding impulse purchases and seeking to control and keep up with financial commitments, including when using the credit card. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-122